2018
DOI: 10.5267/j.msl.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of product quality, medical price and staff skills on patient loyalty via cultural impact in medical tourism

Abstract: The aim of this research is to understand the effect of product quality, medical price and staff skill on patient's loyalty through cultural impact in medical tourism. In this study, three exogenous constructs; namely product quality, medical price, and staff skill constructs were adopted to find their effects on patient's loyalty. Meanwhile, the cultural impact is also adopted as a mediator construct. This study uses confirmatory approach as Covariance based Structural Equation Modeling (CBSEM) for testing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…In this study, patients have become more involved in hospital choice, while many patients do not choose a hospital directly, findings suggest that they often do this indirectly through choice of a personal physician. Patients' satisfaction with hospital treatment positively influences the image of the medical facility (Szyca et al, 2012;Afthanorhan et al, 2018). They found that many factors are involved which are the assessment of the quality of the medical service associated with the rapid solution of the reported problem, staff empathy and attitude, as well as the understanding and precise information.…”
Section: Patients' Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, patients have become more involved in hospital choice, while many patients do not choose a hospital directly, findings suggest that they often do this indirectly through choice of a personal physician. Patients' satisfaction with hospital treatment positively influences the image of the medical facility (Szyca et al, 2012;Afthanorhan et al, 2018). They found that many factors are involved which are the assessment of the quality of the medical service associated with the rapid solution of the reported problem, staff empathy and attitude, as well as the understanding and precise information.…”
Section: Patients' Satisfactionmentioning
confidence: 99%
“…The satisfaction of the patient with the service taken is important in terms of loyalty and positive perception of the hospital (Chi & Gursoy, 2009). It is not possible unsatisfied customer becomes loyal customer while satisfied customer is always a loyal customer (Chang et al, 2013;Afthanorhan et al, 2018).…”
Section: Patients' Loyaltymentioning
confidence: 99%
“…There is no doubt about the increasing market size of medical tourism and the increasing demand for services [14,27,35,[37][38][39][40]. The reasons for the increasing number of medical tourists travelling from developed to developing countries can be economically explained by Oyewole [41].…”
Section: Increased Demandmentioning
confidence: 99%
“…In spite of Korea's popularity as a medical tourism destination, there is a paucity of literature which studies medical tourism in Korea, because Korea has only recently entered the medical tourism market compared to Thailand and Malaysia [15,16,54,56,63]. Among the few reported studies, some focused on analyzing the demand perspectives, such as how cultural differences affect the choice of destination [15,40] and the formation of Japanese tourists' travel plans for medical treatment in Korea [56]. One article investigated the key developmental characteristics of medical tourism in Korea [39].…”
Section: Medical Tourism In South Koreamentioning
confidence: 99%
“…Convergent Validity, which is evaluated through Average Variance Extracted. The construct reliability (CR) is evaluated through computing CR value for every construct(Awang et al, 2018;Afthanorhan et al, 2018;Mohamad et al, 2017Mohamad et al, , 2018Mohamad et al, , 2019. The Confirmatory Factor Analysis outputs are presented inFigure 2.…”
mentioning
confidence: 99%